Analysis of Fat Grafts for Stabilizing Microvascular Pedicle Geometry in Head and Neck Reconstruction - Yagi, Shunjiro; Suyama, Yoshiko; Fukuoka, Kohei; Morita, Maki; Kambe, Miki; Toriyama, Kazuhiro; Kamei, Yuzuru (Journal of Reconstructive Microsurgery Open, 2017)
Background Even after careful microanastomosis, microsurgeons sometimes encounter unexpected twisting, kinking, and destabilizing mechanical forces. In these cases, a small fat graft is a useful technique for stabilizing the pedicle geometry in free flap transfer. However, few reports have provided the details with an analysis of fat graft use. The use of fat grafts for free flap transfer in head and neck reconstruction was reviewed.Materials and Methods This was a retrospective review of 157 patients (116 men, 41 women; average ± SD age: 64 ± 13.1 years) who had undergone head and neck reconstruction with free flap transfer between 2010 and 2016. We used a fat graft to stabilize pedicle geometry to prevent kinking and other problems. Postoperative thrombosis formation and the use of a fat graft at the pedicle depending on recipient vessel selection and reconstructed site were examined.Results In 23 patients (14.6%), fat grafting was performed to correct pedicle geometry. A fat graft was used at the arterial anastomosis in 13 patients and at the venous anastomosis in 10. There were no significant differences in postoperative thrombosis formation depending on the use of a fat graft. However, fat grafts were more likely to be performed with the superior thyroid artery as a recipient artery and in tongue and/or oral cavity reconstruction.Conclusion A fat graft is a reliable and easy procedure to correct pedicle geometry. However, reconstructive surgeons should consider the use of a fat graft based on the selection of the recipient vessels and the recipient site.
Keywords: microsurgery; fat graft; pedicle; head and neck; free flap